-h=-4-2h

Simple and best practice solution for -h=-4-2h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -h=-4-2h equation:


Simplifying
-1h = -4 + -2h

Solving
-1h = -4 + -2h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '2h' to each side of the equation.
-1h + 2h = -4 + -2h + 2h

Combine like terms: -1h + 2h = 1h
1h = -4 + -2h + 2h

Combine like terms: -2h + 2h = 0
1h = -4 + 0
1h = -4

Divide each side by '1'.
h = -4

Simplifying
h = -4

See similar equations:

| 3x-4+4x=11 | | (4k+6)+2(-k+5)=22 | | 9+4x-13=6x+14-2x | | 16x-40=16x+14 | | 8r-5(6-7r)=18-5r | | -3b+7(4b-4)=-(6b-3) | | 1/8=a/56 | | -5.57-4y+11.58=-20 | | .06-.03x+.03=-.01-.01x | | -0.9(3x-6)=-8.1 | | -2x-1=5-5x | | 9x-37=2x+47 | | 60x-100=-22x-264 | | 12+2y=-1 | | -8r+32=-4(3r-1) | | (X+7)+(x+7)2+3x+x+1=182 | | 3x-10+7x-42=180 | | -0.003x^2+x+0.006=0 | | 5z=50 | | 0.5x+10=0.25x+54 | | -5x-31=-9x+37 | | 47.2-81.9= | | 48=4x-4 | | -7x+1=127+7x | | 8r-5(6-7)=18-5r | | 154=12x+10 | | x+5=-4x-4 | | 4x+5=4x-2 | | 11x+13=134 | | 5x-4=2x+-1 | | 2x+3=123 | | -X-4(2x+1z-15)+3z=-20 |

Equations solver categories